Effect of Autologous Cord Blood Infusion on Motor Function and Brain Connectivity in Young Children with Cerebral Palsy: A Randomized, Placebo‐Controlled Trial. (28th October 2017) - Sun, Jessica M.; Song, Allen W.; Case, Laura E.; Mikati, Mohamad A.; Gustafson, Kathryn E.; Simmons, Ryan; Goldstein, Ricki; Petry, Jodi; McLaughlin, Colleen; Waters‐Pick, Barbara; Chen, Lyon W.; Wease, Stephen; et al.
Abstract: Cerebral palsy (CP) is a condition affecting young children that causes lifelong disabilities. Umbilical cord blood cells improve motor function in experimental systems via paracrine signaling. After demonstrating safety, we conducted a phase II trial of autologous cord blood (ACB) infusion in children with CP to test whether ACB could improve function (ClinicalTrials.gov, NCT01147653; IND 14360). In this double‐blind, placebo‐controlled, crossover study of a single intravenous infusion of 1–5 × 10 7 total nucleated cells per kilogram of ACB, children ages 1 to 6 years with CP were randomly assigned to receive ACB or placebo at baseline, followed by the alternate infusion 1 year later. Motor function and magnetic resonance imaging brain connectivity studies were performed at baseline, 1, and 2 years post‐treatment. The primary endpoint was change in motor function 1 year after baseline infusion. Additional analyses were performed at 2 years. Sixty‐three children (median age 2.1 years) were randomized to treatment ( n  = 32) or placebo ( n  = 31) at baseline. Although there was no difference in mean change in Gross Motor Function Measure‐66 (GMFM‐66) scores at 1 year between placebo and treated groups, a dosing effect was identified. In an analysis 1 year post‐ACB treatment, those who received doses ≥2 × 10 7 /kg demonstrated significantly greater increases in GMFM‐66 scores above those predicted by age and severity, as well as in Peabody Developmental Motor Scales‐2 Gross Motor Quotient scores and normalized brain connectivity. Results of this study suggest that appropriately dosed ACB infusion improves brain connectivity and gross motor function in young children with CP. Stem Cells Translational Medicine 2017;6:2071–2078 Abstract : Change in brain connectivity 1 year after autologous cord blood treatment by cell dose. The nodes and edges included are those that demonstrated significantly increased improvement in children receiving high doses compared with those receiving low doses, as indicated by the color chart, with insignificant nodes shown in gray. High dose ≥2 × 10 7 /kg, low dose <2 × 10 7 /kg.